Time Out with Half-Time: Job Sharing in the Nineties - Turner, Linda (Canadian Journal of Counselling and Psychotherapy, 2011)
Job sharing is an alternative form of employment which may often be overlooked by the average worker. Apart from the negative consequences of receiving half the salary of a full-time position, what are some of the benefits enjoyed by people who job share? Eight women were interviewed for this qualitative research study. Rather than simply allowing more time for them to spend with their children or on domestic chores, job sharing provided them with some unanticipated opportunities to enjoy a richer quality of life.